REGIONAL STRATEGY OF UZBEK EXPORT IN THE CONTEXT OF GLOBAL ECONOMIC CHANGES (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the export-import activities of the Republic of Uzbekistan in 2021-2025. During the study, the dynamics of the country's foreign trade structure, territorial distribution, and product groups were studied. Based on statistical data, scientifically based recommendations for increasing export potential have been developed. The research results are of practical importance for the formation of a regional export strategy.